555 The impact of the digitalization to the medical supply chain. (1st September 2016) - Peltoniemi, Teijo; Suomi, Reima
Abstract : Background: Digitalization equalises information asymmetries, which increases economic efficiency and transforms many lines of business. We argue that digitalization can do the same within the medical supply chain. Methods: We utilise conceptual theory building. This is supported by a literature review and an interview conducted with a key actor within the Finnish pharmaceutical arena. Results: 1) Electronic prescription has the potential to increase the information between physician and patient. Some positive results have been obtained relating to medication safety. 2) The generic substitution system has been implemented to decrease the information asymmetry relating to medicine prices. This has had an effect on the annual medicine expenditures in Finland. 3) These developments have however no influence to the lack of patient adherence. It is a form of information asymmetry with a grave impact to the healthcare system. Adherence could be alleviated with digital solutions. These include solutions supporting patient engagement as well as controlled delivery of medicines at home. 4) Outcomes-based medicine tries to decrease the uncertainty in the field of medical care. This can be alleviated with data gathered from the patient with innovations such as wearables. This can have impact also to the moral hazard threat in the health insurance field. 5) Overall, there is more information available on medical treatments, which should be utilised to increase the patient engagement. 6) Medicine spoilage and shortage are severe information asymmetry related problems. Digital systems could support the prediction of the demand and real time tracking of the consumption of medicines. Conclusions: Digitalization could improve the medical supply chain by decreasing the information asymmetries between different actors. Whereas there is some promising development, considerable potential remains still unused.